2021
DOI: 10.1016/j.precamres.2020.106054
|View full text |Cite
|
Sign up to set email alerts
|

The construction mechanism of the Neoproterozoic S-type Sanfang-Yuanbaoshan granitic plutons in the Jiangnan Orogenic Belt, South China: Insights from geological observation, geochronology, AMS and Bouguer gravity modeling

Abstract: The Neoproterozoic S-type granitic plutons, distributed along the suture zone of the Yangtze and Cathaysia blocks, play an important role in the tectonic evolution of the Jiangnan Orogeny.However, few researchers had focused on the scientific issues on the physical construction process of these plutons. Therefore, we carried out multidisciplinary approaches on the Sanfang and Yuanbaoshan plutons in the western Jiangan Orogenic Belt to figure out the construction mechanism of these plutons. Zircon Hf and U-Pb d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…The Yuanbaoshan granitic pluton is a N-S-trending, elliptically shaped batholith that intrudes the Yuxi Formation and yields an age of 838 ± 5 Ma [33]. In addition, there are five NW-SE-trending gabbroic dikes in the mining area, which are thought to be Neoproterozoic in age, although precise ages are not available for these rocks.…”
Section: Geology Of the Jialong Tin Depositmentioning
confidence: 99%
See 1 more Smart Citation
“…The Yuanbaoshan granitic pluton is a N-S-trending, elliptically shaped batholith that intrudes the Yuxi Formation and yields an age of 838 ± 5 Ma [33]. In addition, there are five NW-SE-trending gabbroic dikes in the mining area, which are thought to be Neoproterozoic in age, although precise ages are not available for these rocks.…”
Section: Geology Of the Jialong Tin Depositmentioning
confidence: 99%
“…The granites in the Jiuwandashan area are mainly middle Neoproterozoic in age [20,22,[25][26][27][28]. After folding of the Neoproterozoic Sibao Group, magma was intruded along faults, which formed mafic-ultramafic intrusions and the Motianling, Yuanbaoshan, and other large granitic plutons in the Jiuwandashan area [33]. Previous studies have shown that Neoproterozoic subduction materials were reactivated and formed a series of mafic igneous rocks during late Mesozoic extension [42].…”
Section: Trace Element Constraints On the Source Of Ore-forming Mater...mentioning
confidence: 99%
“…L. Wang et al, , 2014X. L. Wang, Zhou, et al, 2007;Yan et al, 2021). The faults in the region are divided into two sets based on their strikes: NNE-SSW strike and NW-SE-to WNW-ESE-strike.…”
Section: Regional Geologymentioning
confidence: 99%
“…These granitoids have S-type geochemical affinities, suggesting that they were emplaced from magmas generated by crustal thickening as a result of the collision between the Yangtze and Cathaysia blocks (Shu et al, 2021;Yan et al, 2021). The first deformation event D1 occurred after the deposition of the Sibao Group and was contemporaneous with granitoid emplacement within the Sibao Group, before the deposition of the Danzhou Group.…”
Section: Neoproterozoic (840-800 Ma) Crustal Shortening (D1)mentioning
confidence: 99%
See 1 more Smart Citation